Citizenship, politics, difference : perspectives from Sub-Saharan signed language communities - Cooper, Audrey C.; Rashid, Khadijat K.; ebrary, Inc. (Washington, DC : Gallaudet University Press, 2015)
"Sub-Saharan Africa is one of the most linguistically, culturally, and geographically diverse regions of the world, home to more than 2,000 languages. As in the rest of the world, Deaf people live throughout the widely varying sub-Saharan communities, equally rich in their signed languages. An emergent body of scholarly research on sub-Saharan signed languages (SSSL) and related Deaf community organizing has created the opportunity to gather together the informed perspectives presented in this revolutionary collection. Drawing examples from all regions of sub-Saharan Africa--Western, Eastern, Central, and Southern--16 contributors join the volume editors in illuminating the circumstances pertaining to cross-border, cross-regional, and global engagements in sub-Saharan Deaf communities. This collection centers upon two interrelated purposes: to examine sub-Saharan African deaf people's perspectives on citizenship, politics, and difference in relation to SSSL practices, and to analyze SSSL practices in relation to sociopolitical histories and social change interests (including addressing aspects of culture, gender, language usage, race, ethnicity, sexuality, and ability). The editors have organized these themes under three main sections, Sub-Saharan Signed Languages and Deaf Communities, The Politics of Mobilizing Difference, and Citizenship. Such wide-ranging subjects as the ethics of studying Kenyan signed language, sign language and Deaf communities in Eritrea, and overcoming cultural and linguistic barriers to HIV/AIDS education drive home the importance of the unique and varied research in this collection"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Deaf -- Africa, Sub-Saharan.; Sign language; Citizenship -- Africa, Sub-Saharan.; Electronic books